Innovative approaches to reducing workplace accidents in coal mining: Evidence from PMDN IUP companies in South Sumatra - Irwan, Faisal; Yusuf, Maulana; Toha, Taufik; Ibrahim, Eddy; Komar, Syamsul; Putra, Rahmat Wahyudi (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2026)
This study examines the influence of the implementation of the Mining Safety Management System (SMKP) on workplace accident rates within coal mining operations. A quantitative research design was adopted, utilizing survey data obtained from 390 employees working in mining companies operating under IUP PMDN in South Sumatra. The variables investigated consist of technical risk control, adherence to Standard Operating Procedures (SOP), safety training and emergency drills, and the utilization of Personal Protective Equipment (PPE). Data analysis was conducted using multiple linear regression to assess both the individual (partial) and combined (simultaneous) effects of the independent variables on accident rates. The findings indicate that the regression model is statistically significant, with a coefficient of determination (R²) of 0.436, suggesting that 43.6% of the variability in workplace accidents is explained by the variables included in the model. At the individual level, safety training and PPE utilization demonstrate a significant effect on accident rates, whereas technical risk control and SOP compliance do not exhibit a statistically significant influence. These results suggest that behavioral aspects have a more prominent role compared to system-related factors in mitigating workplace accidents. Accordingly, this study underscores the need to prioritize the enhancement of safety training programs, strengthen safety awareness, and ensure consistent PPE compliance as critical strategies for improving safety performance in the mining industry.